Analyzing Language Stylistics of Metaphors in “Lesson Learned” Album by Aziz Hedra: A Literary Study of Metaphors in Song Lyrics - Simanjuntak, Azzura Annisa; Adam, Adam; Dewi, Desi Surlitasari (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study examines the metaphorical language style in Aziz Hedra's album